A high coercive force Nd-Fe-B system sintered magnet and its preparation method and application

By adding Mn and Cu/Al auxiliary alloy powders of Mn and Cu/Al to the Nd-Fe-B system sintered magnets, the grain boundary structure is adjusted, and the problem of limited coercive force enhancement in the prior art is solved, thereby achieving higher coercive force and stable magnetic properties.

CN115083714BActive Publication Date: 2025-03-25YANTAI ZHENGHAI MAGNETIC MATERIAL CO LTD

Patent Information

Application Number
CN202210800345.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-06
Publication Date
2025-03-25
Estimated Expiration
2042-07-06

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the coercive force of sintered magnets in rare earth permanent magnet materials, especially in neodymium iron boron-based materials, where excessive or too little metal addition will lead to a decrease in magnetic performance.

Method used

By adding an appropriate amount of Mn to the Nd-Fe-B system sintered magnet and combining Cu and/or Al auxiliary alloy powder, the grain boundary structure is adjusted to form a beneficial wrapping layer, thereby improving coercive force.

Benefits of technology

It is realized that the coercive force of the sintered magnet is significantly improved while ensuring that the magnetic performance is not reduced, and the problem of limited metal addition amount in the prior art is overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115083714B_ABST
    Figure CN115083714B_ABST
Patent Text Reader

Abstract

The present invention discloses a high coercive force Nd-Fe-B system sintered magnet and a preparation method and application thereof. The sintered magnet comprises the following components based on a mass ratio of 100%: R 26-37wt%, wherein R is at least one rare earth element including Nd; Mn 0.07-0.23wt%; B 0.8-1wt%; M 0.5-4wt%, wherein M comprises Cu and / or Al, and also comprises at least one selected from Co, Ti, Ni, Zr, and Ga; and the remainder is Fe. The present invention prepares a Nd-Fe-B sintered magnet by mixing an auxiliary alloy powder containing Mn with a main Nd-Fe-B alloy powder without Mn. In addition to the Mn element within the scope of the present invention, the auxiliary alloy powder containing Mn must also contain at least one of metal Cu and Al. Mn can replace part of Fe in the main phase, so that the amount of grain boundary beneficial elements dissolved in the main phase is reduced, thereby improving the coercive force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of rare earth permanent magnets, and in particular relates to a high coercive force Nd-Fe-B system sintered magnet and a preparation method and application thereof. Background Art

[0002] Permanent magnet materials are widely used in clean energy fields such as the new energy vehicle industry and wind power generation. The clean energy field is undoubtedly an important development direction in the future. The rapid development of the clean energy field has put forward higher requirements on the magnetic properties of sintered magnets. The increasingly harsh working environment requires sintered magnets to have higher coercivity.

[0003] The optimization of the coercivity of permanent magnet materials has always been a technical difficulty to be overcome. The powder particle size can be reduced through process means, the crystal particle size can be refined, and the coercivity can be improved. However, the refined particle size increases the surface energy of the powder, which can easily lead to abnormal growth of sintered grains. With the continuous advancement of NdFeB technology, the performance breakthrough brought by process means is becoming increasingly weak, and other technologies should be actively adopted.

[0004] In addition to process methods, the grain boundary structure can be adjusted to improve the coercive force. Metals represented by Al and Cu have been proven to effectively improve the wettability of the main phase and the grain boundary phase to improve the coercive force. Taking Al as an example, Al solid dissolves into the main phase, causing the Curie temperature to decrease and the remanence to decrease. Taking Cu as an example, when Cu is distributed at the interface between the main phase and the grain boundary phase, it can effectively improve the coercive force, but when Cu enters the main phase, it causes the magnetic properties to decrease. This type of method of increasing the coercive force by adding metal to adjust the grain boundary structure is subject to the amount of metal added. When the amount of metal added is lower than a certain limit, the magnetic properties are improved ineffectively; when the amount of metal added is higher than a certain limit, the magnetic properties are reduced instead. Therefore, it is necessary to adopt new technologies to adjust the grain boundary structure on the basis of existing technologies in order to achieve higher coercive force indicators.

[0005] In response to the above technical problems, document CN101657863B discloses that in rare earth-iron-boron sintered magnets, the coercive force can be improved by adding Al, and by replacing the iron component with Mn, the reduction of magnetic properties can be suppressed to a minimum and the coercive force can be improved. Document CN102067249B discloses that in rare earth-transition metal-boron sintered magnets, by adding a specified amount of Mn, the amount of Cu added can be increased and the coercive force can be improved. The above documents all propose to add Mn to rare earth-iron-boron sintered magnets to improve the coercive force, and confirm that the addition of Mn can improve the coercive force in sintered magnets, but the range of Mn content in the two documents is different. In Table 4 of Example 4 of document CN101657863B, the highest coercive force value appears when the Mn atomic weight is 0.05%. When the Mn atomic addition exceeds 0.05%, the coercive force improvement effect is not significant; when the Mn atomic weight is 0.4%, the coercive force level is even lower than when the Mn atomic addition is 0.01%. It can be seen that the Mn content is far from "Mn: more than 0.02 atomic % and less than 0.5 atomic %" mentioned in the document.

[0006] Document CN101689416B discloses that adding Pr and Mn within a specified range to a sintered magnet can improve the room temperature coercivity. It also suggests that the technical effect cannot be achieved if the amount of Pr added is lower than the specified amount, but the specific theory is not elaborated. Summary of the invention

[0007] In order to improve the above technical problems, the technical solution of the present invention is as follows:

[0008] A high coercive force Nd-Fe-B system sintered magnet, which comprises the following components based on a mass ratio of 100%:

[0009] R 26-37 wt%, wherein R is at least one rare earth element including Nd;

[0010] Mn 0.07~0.23wt%;

[0011] B 0.8~1wt%;

[0012] M 0.5-4wt%, wherein M includes Cu and / or Al, and also includes at least one selected from Co, Ti, Ni, Zr, and Ga;

[0013] The balance is Fe.

[0014] According to an embodiment of the present invention, the R is 28-36 wt %, and the R includes Nd and at least one selected from Pr, Dy, Ho, and Tb.

[0015] According to an embodiment of the present invention, the Mn is 0.07wt%, 0.08wt%, 0.1wt%, 0.12wt%, 0.14wt%, 0.15wt%, 0.16wt%, 0.17wt%, 0.18wt%, 0.19wt%, 0.2wt%, 0.21wt%, 0.22wt% or 0.23wt%.

[0016] According to an embodiment of the present invention, the B is 0.8wt%, 0.82wt%, 0.84wt%, 0.86wt%, 0.88wt%, 0.9wt%, 0.92wt%, 0.94wt%, 0.95wt%, 0.98wt% or 1wt%.

[0017] According to an embodiment of the present invention, the M is preferably 0.8-3 wt %; the M includes Cu and / or Al, and also includes at least one selected from Co, Ti, Zr, and Ga.

[0018] According to an embodiment of the present invention, the grain size of the high coercive force Nd—Fe—B system sintered magnet is 3 to 6 μm, preferably 3.9 to 4.8 μm.

[0019] The present invention also provides a method for preparing the above-mentioned high coercivity Nd-Fe-B system sintered magnet, the method comprising the following steps:

[0020] (S1) first preparing a Mn-free NdFeB main alloy flake and a Mn-containing auxiliary alloy flake respectively;

[0021] Wherein, the Mn-free NdFeB main alloy flakes include R 29-36wt%, B 0.9-1wt%, M 0.1-3.5wt%, and the balance is Fe;

[0022] The Mn-containing auxiliary alloy flakes include: R 12-37wt%, Mn 1-10wt%; B 0-1wt%, M 0.5-30wt%, and the balance is Fe;

[0023] Preferably, in step (S1), M in the main alloy flakes does not contain Cu and / or Al, M in the auxiliary alloy flakes must contain Cu and / or Al, the content of Cu in the auxiliary alloy flakes is 0-9wt%, the content of Al is 0-8wt%, and the content of Cu and Al is not 0 at the same time;

[0024] (S2) The NdFeB main alloy flakes without Mn and the Mn auxiliary alloy flakes in step (S1) are subjected to hydrogen crushing and air flow grinding to obtain a mixed alloy powder, and the mixed alloy powder is subjected to pressing, sintering and tempering to prepare the high coercive force Nd-Fe-B system sintered magnet.

[0025] According to an embodiment of the present invention, in step (S1), in the Mn-containing auxiliary alloy flakes, the R comprises at least 12 to 30 wt % of Nd.

[0026] According to an embodiment of the present invention, in step (S2), the Mn-free NdFeB main alloy flakes account for 87 to 98 wt% of the total amount of the Mn-free NdFeB main alloy flakes and the Mn-containing auxiliary alloy flakes, for example, it can be 87 wt%, 87.6 wt%, 89 wt%, 91 wt%, 92 wt%, 93 wt%, 95 wt%, 96.3 wt%, 97 wt%, 97.6 wt%, 97.8 wt%, 98 wt%.

[0027] According to an embodiment of the present invention, in step (S2), the mixed alloy powder comprises a Mn-free NdFeB main alloy powder and a Mn-containing auxiliary alloy powder.

[0028] According to an embodiment of the present invention, in step (S2), the mixed alloy powder can be oriented and shaped in a magnetic field, and after shaping, it can be cold isostatically pressed to form a compact.

[0029] According to an embodiment of the present invention, in step (S2), the sintering temperature is 800-1200°C, and the holding time is 3-20 hours. Preferably, a secondary sintering is adopted, the temperature of the first sintering is 900-1200°C, preferably 900-1080°C, and the holding time is 3-8 hours, preferably 6-8 hours; the temperature of the second sintering is 800-1100°C, and the holding time is 3-7 hours.

[0030] Preferably, when the proportion of Mn in the sintered magnet is 0.15-0.23 wt % and the particle size of the alloy powder is 3.0-3.8 μm, the temperature of the first sintering is 900-1050° C. and the holding time is 6-8 h.

[0031] According to an embodiment of the present invention, in step (S2), the tempering treatment is a secondary tempering treatment, for example, the secondary tempering treatment is carried out in a vacuum tempering furnace; the primary tempering temperature is 700-950°C, the holding time is 4-8h, and the secondary tempering temperature is 450-600°C, and the holding time is 4-8h.

[0032] According to an embodiment of the present invention, step (S2) may be, (S2a) subjecting the Mn-free NdFeB main alloy flakes and the Mn-containing auxiliary alloy flakes in step (S1) to hydrogen crushing and air flow grinding respectively to obtain Mn-free NdFeB main alloy powder and Mn-containing auxiliary alloy powder respectively, and mixing the Mn-free NdFeB main alloy powder and the Mn-containing auxiliary alloy powder evenly to obtain a mixed alloy powder, and subjecting the powder to pressing, sintering and tempering treatment to prepare the high coercive force Nd-Fe-B system sintered magnet.

[0033] According to the present invention, in step (S2a), the average particle size of the Mn-free NdFeB main alloy powder is 3.0-3.8 μm, for example, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm or 3.8 μm.

[0034] Preferably, the Mn-containing auxiliary alloy powder has an average particle size of 3 to 4 μm, for example, 3 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm, 3.8 μm, 3.9 μm or 4 μm.

[0035] According to an embodiment of the present invention, step (S2) can also be: (S2b) mixing the Mn-free NdFeB main alloy flakes and the Mn-containing auxiliary alloy flakes in step (S1), hydrogen crushing and air flow grinding to obtain a mixed alloy powder, and then pressing, sintering and tempering to prepare the high coercive force Nd-Fe-B system sintered magnet.

[0036] According to the present invention, in step (S2b), the average particle size of the mixed alloy powder is 3.0-3.8 μm, for example, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm, 3.5 μm, 3.6 μm, 3.7 μm or 3.8 μm.

[0037] As an exemplary embodiment of the present invention, the method for preparing the high coercive force Nd-Fe-B system sintered magnet specifically comprises the following steps:

[0038] (1) preparing a Mn-free NdFeB main alloy flake and a Mn-containing auxiliary alloy flake respectively;

[0039] (2) mixing the Mn-free NdFeB main alloy flakes and the Mn-containing auxiliary alloy flakes according to a certain proportion, and then subjecting the mixture to hydrogen explosion-air flow milling to obtain a mixed alloy powder, wherein the mixed alloy powder comprises the Mn-free NdFeB main alloy powder and the Mn-containing auxiliary alloy powder;

[0040] Alternatively, the Mn-free NdFeB main alloy flakes and the Mn-containing auxiliary alloy flakes are subjected to hydrogen explosion-air flow milling to obtain Mn-free NdFeB main alloy powder and Mn-containing auxiliary alloy powder respectively, and the main alloy powder and the auxiliary alloy powder are mixed, wherein the particle size of the Mn-free NdFeB main alloy powder is 3.0-3.8 μm, and the particle size of the Mn-containing auxiliary alloy powder is 3.0-4.0 μm;

[0041] The Mn-free NdFeB main alloy flakes account for 87-98wt% of the total amount of the Mn-free NdFeB main alloy flakes and the Mn-containing auxiliary alloy flakes;

[0042] (3) orienting and shaping the mixed alloy powder uniformly mixed in step (2) in a magnetic field, and forming the green compact by cold isostatic pressing, and sintering the green compact in a vacuum sintering furnace, wherein the first sintering temperature is 900-1200° C. and the holding time is 3-8 h; and then sintering the green compact for a second time, wherein the second sintering temperature is 800-1100° C. and the holding time is 3-7 h, to obtain a green compact;

[0043] When the Mn content in the sintered magnet is 0.15-0.23wt% and the alloy powder particle size is 3.0-3.8μm, the first sintering temperature is 900-1050℃ and the holding time is 6-8h;

[0044] (4) The blank in step (3) is subjected to two-stage tempering in a vacuum tempering furnace, wherein the first-stage tempering temperature is 700-950° C., the holding time is 4-8 hours, and the second-stage tempering temperature is 450-600° C., the holding time is 4-8 hours, to prepare the high coercive force Nd-Fe-B system sintered magnet.

[0045] The present invention also provides the application of the high coercive force Nd-Fe-B system sintered magnet in the fields of new energy automobile industry, wind power generation, etc.

[0046] Beneficial effects of the present invention:

[0047] The present invention prepares Nd-Fe-B sintered magnets by mixing auxiliary alloy powder containing Mn with main NdFeB alloy powder without Mn. The auxiliary alloy powder containing Mn must contain at least one of metals Cu and Al in addition to the Mn element within the scope of the present invention. Mn can replace part of Fe in the main phase, so that the amount of grain boundary beneficial elements dissolved in the main phase is reduced, thereby improving the coercive force. The present invention also uses Pr to replace part of Nd. In addition to ensuring that Nd is the main element in the main phase, the amount of Pr added is not related to the amount of Mn added, which may be because Pr does not react after being added to the main phase.

[0048] In the prior art, low melting point metals Cu and Al are generally used to improve the grain boundary structure and increase the coercive force. Al has a high solubility in the main phase, and entering the main phase will damage the magnetic properties. Cu can improve the wettability of the grain boundary phase in the grain boundary and promote the formation of a thin layer of grain boundary phase. Therefore, the addition amount of Al and Cu should be controlled within a suitable range. The present invention adds Mn in the form of auxiliary alloy powder. When the Mn element replaces the Fe element, a Mn coating layer is formed, which reduces the entry of Cu and Al into the main phase and improves the grain boundary structure. Therefore, compared with the alloy smelting method in the prior art, the dual alloy method of the present invention can obtain an increase in the coercive force of the sintered magnet, while overcoming the problem of a large reduction in residual magnetism brought about by the prior art.

[0049] The present invention uses air flow milling to crush the main alloy flakes and auxiliary alloy flakes into the range of 3.0-3.8μm and 3-4μm respectively, or mixes the main alloy flakes and auxiliary alloy flakes and crushes them into 3.0-3.8μm, so that smaller grains can be obtained; at the same time, the grain boundary elements such as Mn, Cu, Al added to the auxiliary alloy can be more fully and evenly wrapped around the main phase grains to strengthen the grain boundaries. Furthermore, when the particle size of the mixed alloy powder is reduced, the surface energy increases sharply. Under the premise of ensuring sufficient density of the sintered body, a sintered magnet with higher coercivity can be prepared by controlling the sintering temperature and sintering time. The present invention also found that when the proportion of Mn in the sintered magnet is 0.15-0.23wt%, and the alloy powder particle size is 3.0-3.8μm, the sintering time is appropriately extended at a sintering temperature of 900-1050°C, and a higher coercivity can be obtained under the same tempering process.

[0050] The present invention provides a method for preparing a Nd-Fe-B system sintered magnet with high coercivity by using a dual alloy method. The method comprises mixing a main alloy powder with an auxiliary alloy powder containing Mn, Cu and / or Al, adjusting the sintering temperature, obtaining a uniform and continuous grain boundary phase, thereby improving the coercivity. When the grain size is minute, a sintered magnet with higher coercivity can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 It is a trend chart of the change of Hcj of the sintered magnets in Examples 3, 8-16 and Comparative Examples 9-13 with the amount of Mn added.

[0052] Figure 2 It is a trend chart of the average particle size of the mixed alloy powder in Examples 17-21 and Comparative Examples 14-18 and the grain size and coercive force of the sintered magnet. DETAILED DESCRIPTION

[0053] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0054] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0055] Examples 1-6, Comparative Examples 1-6

[0056] Prepared as follows,

[0057] (1) According to the proportions of each main alloy flake in Table 1, the raw materials are weighed (the units are all wt%), the prepared raw materials are melted in an argon atmosphere, and then poured onto a quenching roller to form a Mn-free NdFeB main alloy flake (i.e., the main alloy in Table 1). Similarly, the auxiliary alloy raw materials are melted and poured in an argon atmosphere to form a Mn-containing auxiliary alloy flake (i.e., the auxiliary alloy in Table 1), the main alloy flakes and the auxiliary alloy flakes are mixed according to the proportion, and then crushed by hydrogen and air flow milling to obtain a mixed alloy powder with uniform particle size. The particle size of the mixed alloy powder is shown in Table 2;

[0058] (2) Orient and shape the mixed alloy powder in step (1) in a magnetic field, and after forming, form a green compact by cold isostatic pressing. Perform secondary sintering heat treatment on the green compact according to the sintering temperature and sintering time in Table 2.

[0059] (3) The blank was subjected to two-stage tempering in a vacuum tempering furnace, with the first-stage tempering temperature being 800°C and the holding time being 5 h, and the second-stage tempering temperature being 500°C and the holding time being 5 h, to obtain a sintered magnet.

[0060] Example 7

[0061] The difference between Example 7 and Examples 1-6 is that:

[0062] (1) The proportions of each element in Example 7 are as shown in Table 1. The raw materials are weighed according to the proportions of each main alloy flake in Table 1 (the units are all wt%), the prepared raw materials are melted in an argon atmosphere, and then poured onto a quenching roller to form a Mn-free NdFeB main alloy flake (i.e., the main alloy in Table 1). Similarly, the auxiliary alloy raw material is melted and poured in an argon atmosphere to form a Mn-containing auxiliary alloy flake (i.e., the auxiliary alloy in Table 1). The prepared main alloy flakes and auxiliary alloy flakes are respectively subjected to hydrogen crushing and air flow mill crushing to obtain a main alloy powder and auxiliary alloy powder with uniform particle size, respectively. The average particle size of the main alloy powder is 3.4μm, and the average particle size of the auxiliary alloy powder is 3.4μm. The main alloy powder and auxiliary alloy powder are evenly mixed to obtain a mixed alloy powder.

[0063] (2) Orient and shape the mixed alloy powder in step (1) in a magnetic field, and after forming, form a green compact by cold isostatic pressing. Perform secondary sintering heat treatment on the green compact according to the sintering temperature and sintering time in Table 2.

[0064] (3) The blank was subjected to two-stage tempering in a vacuum tempering furnace, with the first-stage tempering temperature being 800°C and the holding time being 5 h, and the second-stage tempering temperature being 500°C and the holding time being 5 h, to obtain a sintered magnet.

[0065] Comparative Examples 7-8

[0066] (1) According to the alloy composition ratio in Table 1, weigh the raw materials (the unit is wt%), take the prepared raw materials and melt them in an argon atmosphere, then pour them onto a quenching roller to form flakes, and then crush them by hydrogen crushing and air flow grinding to obtain NdFeB alloy powder with uniform particle size.

[0067] (2) Orient and shape the NdFeB alloy powder in step (1) in a magnetic field, and after forming, form a green compact by cold isostatic pressing. Perform secondary sintering heat treatment on the green compact according to the sintering temperature and sintering time in Table 2.

[0068] (3) The blank was subjected to two-stage tempering in a vacuum tempering furnace, with the first-stage tempering temperature being 800°C and the holding time being 5 h, and the second-stage tempering temperature being 500°C and the holding time being 5 h, to obtain a sintered magnet.

[0069] Table 1 Alloy composition of Examples 1-7 and Comparative Examples 1-8

[0070]

[0071] Table 1 (Continued) Alloy composition of Examples 1-7 and Comparative Examples 1-8

[0072]

[0073]

[0074] The “total content” in Table 1 refers to the content of each element in the prepared sintered magnet.

[0075] Table 2 Process parameters of Examples 1 to 7 and Comparative Examples 1 to 8

[0076]

[0077] Table 3 Magnetic properties results of Examples 1 to 7 and Comparative Examples 1 to 8

[0078] Br / T Hcj / (KA / m) (BH)max / kJ / m^3 Hk / Hcj <![CDATA[Density (g / cm 3 )]]> Example 1 1.441 1470 405.9 0.977 7.53 Example 2 1.378 1389 384 0.987 7.55 Example 3 1.300 1708 334 0.977 7.53 Example 4 1.389 1582 325 0.985 7.51 Example 5 1.375 2043 415 0.974 7.53 Example 6 1.421 1386 398.2 0.975 7.51 Example 7 1.421 1376 397.6 0.974 7.53 Comparative Example 1 1.448 1421 406.3 0.980 7.52 Comparative Example 2 1.382 1325 382 0.986 7.56 Comparative Example 3 1.381 1349 380 0.983 7.53 Comparative Example 4 1.312 1660 334 0.969 7.52 Comparative Example 5 1.401 1530 321 0.988 7.52 Comparative Example 6 1.387 1860 416 0.963 7.50 Comparative Example 7 1.446 1442 404.1 0.976 7.52 Comparative Example 8 1.423 1365 398.2 0.977 7.53

[0079] By comparing the data of Example 1 and Comparative Example 1, it can be seen that Comparative Example 1 does not contain Mn element. Compared with the magnetic measurement results of the two, the present invention contains Mn element, so the Hcj of the prepared sintered magnet is higher and the decrease of Br is very small.

[0080] Comparing Example 1 with Comparative Example 7, the Hcj of the sintered magnet prepared by the dual alloy preparation process of the present invention is significantly improved. Similarly, comparing Example 6 with Comparative Example 8, the Hcj of the sintered magnet prepared by the dual alloy preparation process is significantly improved. It can be seen that the Mn added to the sintered magnet in the form of auxiliary alloy in the present invention has a higher coercive force.

[0081] Comparing Example 2 with Comparative Examples 2 and 3, Example 2 adds Al and Cu to the auxiliary alloy, and adds Mn to the auxiliary alloy; Comparative Example 2 only adds Mn to the auxiliary alloy, and does not add Al and Cu to the alloy; Comparative Example 3 adds Al and Cu to the auxiliary alloy, and adds Mn to the main alloy. From the magnetic property results in Table 3, although Mn is added in Comparative Examples 2 and 3, Al and Cu are not added to the auxiliary alloy, resulting in insufficient Hcj of the sintered magnet; adding Mn in the form of the main alloy will also result in insufficient Hcj of the sintered magnet. Similarly, comparing Example 5 and Comparative Example 6, Example 5 contains Al, Cu and Mn in the auxiliary alloy, and Comparative Example 6 only adds Mn to the auxiliary alloy. From the magnetic property results in Table 3, the Hcj of Comparative Example 6 is lower.

[0082] It can be seen that the present invention adds Al and / or Cu to the auxiliary alloy and needs to add Mn at the same time to prepare a sintered magnet with excellent coercivity. In summary, the Mn element of the present invention is added to the auxiliary alloy, acts on the grain boundary, and after forming a surrounding layer at the grain boundary, it can reduce the entry of Cu and Al into the main phase, which can effectively improve the coercivity.

[0083] Comparing Example 6 and Example 7, the main alloy flakes and auxiliary alloy flakes of Example 6 are mixed before hydrogen crushing and then further crushed by air flow milling. The main alloy flakes and auxiliary alloy flakes of Example 7 are respectively subjected to hydrogen crushing and air flow milling to obtain main alloy powder and auxiliary alloy powder, respectively, and then the main alloy powder and auxiliary alloy powder are mixed. It can be seen from Table 3 that the two mixing methods have little effect on the magnetic properties.

[0084] Comparing Example 3 with Comparative Example 4, Example 3 contains 0.12wt% Mn, and Comparative Example 4 contains 0.3wt% Mn; comparing Example 4 with Comparative Example 5, Example 4 contains 0.14wt% Mn, and Comparative Example 5 contains 0.25wt% Mn. From the magnetic property results in Table 3, it can be seen that the sintered magnet prepared by the present invention has better performance, which means that when the amount of Mn added exceeds a certain limit, the magnetic properties of the sintered magnet will be reduced.

[0085] Examples 8-16, Comparative Examples 9-13

[0086] (1) Examples 8-16 and Comparative Examples 9-13 Based on Example 3, only the total amount of Mn added was changed. The total Mn content of Examples 8-16 was 0.07wt%, 0.08wt%, 0.1wt%, 0.14wt%, 0.16wt%, 0.18wt%, 0.2wt%, 0.22wt%, 0.23wt%, and the Mn content of Comparative Examples 9-12 was 0.00wt%, 0.24wt%, 0.26wt%, 0.28wt%, 0.3wt%. Raw materials (in wt%) were weighed for each main alloy flake ratio, and the prepared raw materials were melted in an argon atmosphere, and then cast onto a quenching roller to prepare a Mn-free NdFeB main alloy flake. Similarly, the auxiliary alloy raw material is melted and cast in an argon atmosphere to form Mn-containing auxiliary alloy flakes. The main alloy flakes and the auxiliary alloy flakes are mixed according to a certain proportion, and then crushed by hydrogen and air flow milling to obtain a uniform mixed alloy powder with an average particle size of 3.7 μm.

[0087] (2) The mixed alloy powder in step (1) is oriented and shaped in a magnetic field, and after forming, a green compact is formed by cold isostatic pressing. The green compact is subjected to a primary sintering at a temperature of 1060° C. for 5.4 hours, and then a secondary sintering at a temperature of 1080° C. for 5.5 hours.

[0088] (3) The blank was subjected to two-stage tempering in a vacuum tempering furnace, with the first-stage tempering temperature being 800°C and the holding time being 5 h, and the second-stage tempering temperature being 500°C and the holding time being 5 h, to obtain a sintered magnet.

[0089] The coercivity of Example 3, Examples 8-16, and Comparative Examples 9-13 varies with the amount of Mn added. Figure 1 As shown, from Figure 1 It can be seen that when only the amount of Mn added is changed and other factors remain unchanged, the coercivity is highest when the Mn content is 0.17-0.23%.

[0090] In summary, the preferred range of Mn added to the auxiliary alloy is 0.17-0.23%.

[0091] Examples 17 to 21, Comparative Examples 14 to 18

[0092] (1) Weigh the raw materials according to the proportions in Table 4 (all in wt%), melt the prepared raw materials in an argon atmosphere, and then pour them onto a quenching roller to make a Mn-free NdFeB main alloy flake; similarly, melt the auxiliary alloy raw materials in an argon atmosphere and pour them into a Mn-containing auxiliary alloy flake. The main alloy flakes and the auxiliary alloy flakes are mixed in proportion, and then crushed by hydrogen and air flow milling to obtain a mixed alloy powder with uniform particle size as shown in Table 5; wherein, Examples 17 to 21 and Comparative Examples 14 to 18 all use the same raw materials;

[0093] (2) Orient and shape the mixed alloy powder in step (1) in a magnetic field, and after forming, form a green compact by cold isostatic pressing. Perform secondary sintering heat treatment on the green compact according to the sintering temperature and sintering time in Table 5.

[0094] (3) The blank was subjected to two-stage tempering in a vacuum tempering furnace, with the first-stage tempering temperature being 800°C and the holding time being 5 h, and the second-stage tempering temperature being 500°C and the holding time being 5 h, to obtain a sintered magnet.

[0095] Table 4 Composition table of Examples 17 to 21 and Comparative Examples 14 to 18

[0096]

[0097] The “total content” in Table 4 refers to the content of each element in the prepared sintered magnet.

[0098] Table 5 Preparation process and performance of Examples 17 to 21 and Comparative Examples 14 to 18

[0099]

[0100] It can be seen from Table 5 that refining the grains of sintered magnets can effectively improve the coercive force.

[0101] Figure 2 The average particle size, grain size, and coercivity of the mixed alloy powders in Examples 17-21 and Comparative Examples 14-18 are shown in Figure 5. By adjusting the average particle size of the mixed powders, the growth of magnet grains can be controlled within a specific temperature range. The preferred grain size is 3.9 to 4.8 μm. Figure 2 It can be seen that when the average particle size of the mixed alloy powder is between 3.0 and 3.8 μm, the coercivity is the best. When the particle size of the mixed alloy powder is less than 3.0 μm, over-sintering is likely to occur, and the coercivity drops sharply. When the particle size of the mixed alloy powder is greater than 3.8 μm, the uniformity of the product grain size cannot be effectively controlled, and the product grain size is greater than 4.8 μm.

[0102] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high coercive force Nd-Fe-B system sintered magnet, characterized in that: The sintered magnet comprises the following components based on a mass ratio of 100%: R 26-37wt%, wherein R is at least one rare earth element including Nd; Mn 0.12~0.23wt%; B 0.8~1wt%; M 0.5-4wt%, wherein M includes Cu and / or Al, and also includes at least one selected from Co, Ti, Ni, Zr, and Ga; The balance is Fe; The magnet is prepared by using Mn-free NdFeB main alloy flakes and Mn-containing auxiliary alloy flakes; Wherein, the Mn-free NdFeB main alloy flakes include R 29-36wt%, B 0.9-1wt%, M 0.1-3.5wt%, and the balance is Fe; The Mn-containing auxiliary alloy flakes include: R 12-37wt%, Mn 1-10wt%; B 0-1wt%, M 0.5-30wt%, and the balance is Fe; The M in the main alloy flakes does not contain Cu and Al, while the M in the auxiliary alloy flakes must contain Cu and Al. The content of Cu in the auxiliary alloy flakes is 0-9wt%, the content of Al is 0-8wt%, and the content of Cu and Al is not 0 at the same time.

2. The sintered magnet according to claim 1, characterized in that The grain size of the high coercive force Nd-Fe-B system sintered magnet is 3-6 μm.

3. The method for preparing a sintered magnet according to claim 1 or 2, characterized in that: The method comprises the following steps: (S1) first preparing a Mn-free NdFeB main alloy flake and a Mn-containing auxiliary alloy flake respectively; (S2a) subjecting the Mn-free NdFeB main alloy flakes and the Mn-containing auxiliary alloy flakes in step (S1) to hydrogen crushing and air flow grinding to obtain Mn-free NdFeB main alloy powder and Mn-containing auxiliary alloy powder, respectively, and mixing the Mn-free NdFeB main alloy powder and the Mn-containing auxiliary alloy powder to obtain a mixed alloy powder, and subjecting the mixed alloy powder to pressing, sintering and tempering to prepare the high coercive force Nd-Fe-B system sintered magnet; In step (S2a), the average particle size of the Mn-free NdFeB main alloy powder is 3.0-3.8 μm; the average particle size of the Mn-containing auxiliary alloy powder is 3-4 μm; Alternatively, (S2b) mixing the Mn-free NdFeB main alloy flakes and the Mn-containing auxiliary alloy flakes in step (S1), crushing with hydrogen, jet milling to obtain a mixed alloy powder, and subjecting the mixed alloy powder to pressing, sintering and tempering to obtain the high coercive force Nd-Fe-B system sintered magnet; In step (S2b), the average particle size of the mixed alloy powder is 3.0-3.8 μm.

4. The method for preparing a sintered magnet according to claim 3, characterized in that: In step (S1), in the Mn-containing auxiliary alloy flakes, the R comprises at least 12-30wt% Nd.

5. The method for preparing a sintered magnet according to claim 3, characterized in that: In step (S2a), the Mn-free NdFeB main alloy flakes account for 87-98wt% of the total amount of the Mn-free NdFeB main alloy flakes and the Mn-containing auxiliary alloy flakes.

6. The preparation method according to claim 3, wherein in step (S2b), the sintering temperature is 800-1200°C and the insulation time is 3-20 hours.

7. The preparation method according to claim 6, wherein the secondary sintering is adopted, the temperature of the first sintering is 900-1200°C, and the holding time is 3-8 hours; the temperature of the second sintering is 800-1100°C, and the holding time is 3-7 hours.

8. According to the preparation method of claim 3, when the proportion of Mn in the sintered magnet is 0.15-0.23wt% and the particle size of the alloy powder is 3.0-3.8μm, the temperature of the first sintering is 900-1050°C and the holding time is 6-8h.

9. The method for preparing a sintered magnet according to claim 3, characterized in that: In step (S2b), the tempering treatment is secondary tempering; the primary tempering temperature is 700-950°C, the holding time is 4-8h, and the secondary tempering temperature is 450-600°C, the holding time is 4-8h.

10. Application of the sintered magnet according to claim 1 or 2 in the new energy automobile industry and wind power generation field.

Citation Information

Patent Citations

  • R-T-B based sintered magnet

    CN101657863B

  • R-T-B sintered magnet

    CN101689416B

  • R-T-Cu-Mn-B type sintered magnet

    CN102067249B

  • R-T-B based sintered magnet

    CN101657863A

  • Sintermagnet auf R-T-B Basis

    CN107039136A

Cited By

  • High-coercivity nd-fe-b series sintered magnet and preparation method and application thereof

    WO2024007808A1